Hip Stability May Influence the Development of Greater Trochanteric Pain Syndrome: A Case-Control Study of Consecutive Patients. Issue 11 (3rd November 2020) - Goldman, LCDR Ashton H.; Land, ENS Vaughn; Adsit, Matthew H.; Balazs, CDR George C.
Background: Greater trochanteric pain syndrome (GTPS) is thought to relate primarily to tendinosis/tendinopathy of the hip abductors. Previous studies have suggested that certain anatomic factors may predispose one to development of the condition. Hypothesis: It was hypothesized that intrinsic acetabular bony stability of the hip is related to the development of GTPS. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 198 consecutive patients diagnosed with GTPS were compared with 198 consecutive patients without clinical evidence of GTPS. Electronic health records of the included patients were examined; data recorded included patient age, sex, race, and body mass index (BMI). Standing anteroposterior radiographs were evaluated by 2 blinded examiners who measured the Tönnis angle, lateral center-edge angle (LCEA), and acetabular depth/width ratio (ADW) and assessed for the presence of a posterior wall sign. The number of dysplastic measures was recorded for each patient based on published norms. Associations between radiographic and patient variables versus the presence or absence of GTPS were determined. Factors with univariate associations where P < .20 were included in a binary logistic regression model to identify independent predictors of the presence of GTPS. Results: There was no difference between groups in terms of age, BMI, or race. There were significantly more women than men in the GTPS group (71% vs 30%; P < .001). Intraclass correlation coefficients were good for the LCEA (0.82) and Tönnis angle (0.82) and poor (0.08) for the ADW. Kappa was moderate for the presence of a posterior wall sign (0.51). An increased Tönnis angle, decreased ADW, and ADW <0.25 were significantly associated with the presence of GTPS. The binary logistic regression model identified an increased Tönnis angle ( P < .010) and female sex ( P < .001) as independent risk factors for GTPS. Conclusion: Based on this preliminary retrospective study, decreased intrinsic acetabular bony stability of the hip may be associated with an increased risk of GTPS.